The Polar Mediterranean Imaginary. A Renewed Paradigm by Vilhjalmur Stefansson - Santiago Villalobos Dantas (Nordicum-Mediterraneum, 2024)
Southern social imaginaries have typically conceived of the North as a frozen and inhospitable area, depriving it of much interest. However, during the first part of the 20th century, the anthropologist and explorer Vilhjalmur Stefansson unveiled many mysteries about the Arctic. Throughout his life and writings, he tried to modify many inaccurate and now old-fashioned imaginings and imaginaries about the Arctic. The concept of the Polar Mediterranean Imaginary was thus proposed by him, whereby the Arctic region could be seen as a place similar to the Mediterranean region, i.e., an important socio-cultural, economic and political hub. Past and present events (e.g., global conflicts, scientific and technologic developments) contribute also to determining how the Arctic is shaped and understood today. The contemporary twin trends of globalization and climate change are making the North more and more globally connected and interconnected, especially through the rise of transpolar routes, which represent an opportunity for the affirmation of the Arctic’s central role, precisely along the lines envisioned by Vilhjalmur Stefansson and his Polar Mediterranean Imaginary one hundred years ago.